KEKUATAN HUKUM AKTA NOTARIIL PERIKATAN JUAL BELI ATAS TANAH DI KABUPATEN SLEMAN - , Eni Wijiastuti, SH ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The purpose of this study to determine the legal power of the agreement notary deed of sale and purchase of land in Sleman and to determine the legal effect to the parties in the sale and purchase agreement of land made by the parties. This study uses empirical research methods juridical meaning this research is more focused field research to obtain primary data in addition to the research literature that point to obtain secondary data. Data were analyzed and interpreted using qualitative methods aimed at classifying and selecting the data obtained from field research by the quality and the truth, then connected with theories derived from literary studies to obtain answers to the problems posed. The results showed that in fact, even though the notarized deed of sale and purchase agreement on land considered valid if it is eligible materiilnya but the deed is a legal agreement is not strong, so it can not provide definitive legal protection for the parties, especially the buyer. This can happen if after doing the deed of making the sale and purchase agreement the purchaser is not immediately followed by a sale deed to be done in the presence of PPAT, so that the legal effect to the parties in a land purchase agreement made by the parties in order to be Tax costs and BPHTB in the end, if there is one party who then becomes the risk of breach of contract for the parties who made it, in this case is the buyer. Deed can not be used as proof of ownership of land has been purchased, it should be the buyer must immediately register the rights over land ownership in order to obtain sound legal certainty in the form of certificates of land, as stipulated in Government Regulation No. 24 of 1997 on Land Registration. Notary as a public official, should also be able to provide legal protection and legal certainty for communities in need, one of which provides information on the law or give legal advice to the parties that would make the deed in the workplace, so no one can harm the parties' future .